(The Effect of Corn and Soybean Proportion with Corn Seed Shape to the Nature of Tempe) - Mochamad Noerdin N.K; Imas Siti S.; Betty Dewi S (Warta Industri Hasil Pertanian, 1994)
The study was conducted to find out the characteristics of tempe made from the mixture of soybean (Glycine max) and corn (Zea mays) which was then compared with those of tempe from soybean. The proprtion of soybean and corn was 9:1 to 5:5. Corn used was the whole corn and corn grits, and all mixtures/proportion produced tempe similar with those made from soybean. Protein content of tempe made from the proportion of soybean and corn 9:1 was in accord with the requirement of the Indonesian Industrial Standard (SII) 0271-80.Tempe with corn grits mixture was prefered in therm taste, aroma, colour,apperance, and its general characteristics.